Effect of ultrafine grinding and ultrasonication duration on the performance of polyvinyl alcohol (PVA) agave gigantea cellulose micro fiber (CMF) bio-composite film - Edi, Syafri; Jamaluddin, Jamaluddin; Nasmi, Herlina Sari; Melbi, Mahardika; Lisman, Suryanegara; Rafles, Sinaga; Ferriawan, Yudhanto; Rahadian, Zainul; Agus, Nugroho; Anish, Khan; Mohammad, A. Wazzan (Taylor & Francis Group, 2023)
This paper aims to assess the effect of ultrafine grinding and ultrasonication treatment on the bio-composite characteristics of polyvinyl alcohol (PVA) Agave gigantea (AG) Cellulose Micro Fiber (CMF) bio-composite film performance. This study included five different types of samples. FESEM investigation of PVA/CMF revealed a fiber diameter of 10–15 μm. According to X-ray diffraction, the CMF bio-composite has the highest crystallinity index (87%). The bio-composite film was as transparent as the pure PVA film, demonstrating that the CMF was uniformly dispersed throughout the film. Tensile testing revealed that the ultrafine grinding and ultrasonication treatment for 2 h (PVA/U2) increased tensile strength by 43% compared to the untreated PVA/CMF sample. This finding is confirmed by thermogravimetry analysis (TGA) and derivative (DTG) analyses, which show that the PVA/U2 sample has the most significant degree of thermal stability when compared to other samples. An ANOVA output supports the results of this experiment with an R2 value of 0.94600232 at a 95% confidence level. The p-value of 0.000079 and F-value of 10.80004 for ultrafine grinding and ultrasonication duration on AG leaf-based PVA bio-composite revealed a statistically significant influence on the studied parameters.